1961
DOI: 10.1099/00221287-26-1-141
|View full text |Cite
|
Sign up to set email alerts
|

Metschnikowiella zobellii sp.nov. and M. krissii sp.nov., two Yeasts from the Pacific Ocean Pathogenic for Daphnia magna

Abstract: SUMMARYMetschnikowiella xobellii sp.nov. and M . krissii sp.nov. are described and Latin diagnoses given. Both species form on VS agar (Wickerham, 1951) only from sea water, 1-57/100 ml.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

1964
1964
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 3 publications
0
5
0
1
Order By: Relevance
“…nov. and M. krissii sp. nov., 2 yeasts from the Pacific Ocean, are pathogenic for Daphnia magna (Van Uden & Castelo-Branco 1961).…”
Section: Introductionmentioning
confidence: 99%
“…nov. and M. krissii sp. nov., 2 yeasts from the Pacific Ocean, are pathogenic for Daphnia magna (Van Uden & Castelo-Branco 1961).…”
Section: Introductionmentioning
confidence: 99%
“…As van Uden commented subsequently [180], none of the Metschnikowia species was isolated in pure culture by their authors, their descriptions being based on morphological observations of the yeasts in the hosts on which they were parasitic. This was so until van Uden, himself, obtained pure cultures of M. krissii and M. zobellii from marine sources [253].…”
mentioning
confidence: 99%
“…Physiologically they may be differentiated by the much higher osmotolerance of M. zobellii and the stronger assimilation of D-glucitol and glucono-8-lactone by that species. van Uden and Castelo-Branco (1961) also reported that M . zobellii differs from M. krissii by its capacity to assimilate D-glucosamine, a compound which we have found extremely useful in species differentiation.…”
Section: Discussionmentioning
confidence: 93%